Evaluation of Retinal Microvascular Perfusion Changes in Patients with Celiac Disease. (17th November 2022) - Erdem, Seyfettin; Ucmak, Feyzullah; Karahan, Mine; Ava, Sedat; Dursun, Mehmet Emin; Dursun, Birgul; Hazar, Leyla; Yolaçan, Ramazan; Keklikci, Ugur
ABSTRACT: Purpose: We aimed to determine whether there are retinal microvascular changes in patients with celiac disease (CD). Methods: A total of 30 patients with CD (group 1) and 30 healthy controls (group 2) were included in this study. AngioVue optical coherence tomography angiography (OCTA) device was used to evaluate the retinal microvascular structure. Results: Some of the values of both optic nerve head (ONH) vessel density (VD) and radial peripapillary capillary VDs were found to be significantly lower in group 1 than in group 2. These 2 groups were similar except for one of the parameters of superficial capillary plexus VD (SCP-VD), whereas it was found that deep capillary plexus VD (DCP-VD) was lower in group 1 than in group 2 except for the foveal area. Conclusion: It was determined that some VDs obtained from the ONH and DCP-VD obtained from most areas of the macular region were significantly lower.